2022
DOI: 10.1017/aog.2023.17
|View full text |Cite
|
Sign up to set email alerts
|

Dark ice in a warming world: advances and challenges in the study of Greenland Ice Sheet's biological darkening

Abstract: The surface of the Greenland Ice Sheet is darkening, which accelerates its surface melt. The role of glacier ice algae in reducing surface albedo is widely recognised but not well quantified and the feedbacks between the algae and the weathering crust remain poorly understood. In this letter, we summarise recent advances in the study of the biological darkening of the Greenland Ice Sheet and highlight three key research priorities that are required to better understand and forecast algal-driven melt: (i) ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…It has recently been suggested that microbes—and especially bacteria—can be transported through the weathering crust, for instance from and into cryoconite holes (Cook et al 2016 ), in particular considering that surface meltwaters consistently contain about 10 4 cells ml −1 (Stevens et al 2022 ). The controls on transport of microbial cells through the weathering crusts remains, however, one of the outstanding questions (Halbach et al 2023 ). The standing theory for inoculation of the supraglacial environments by bacteria is that they are delivered through aerial deposition (Šantl-Temkiv et al 2018 , Cameron et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that microbes—and especially bacteria—can be transported through the weathering crust, for instance from and into cryoconite holes (Cook et al 2016 ), in particular considering that surface meltwaters consistently contain about 10 4 cells ml −1 (Stevens et al 2022 ). The controls on transport of microbial cells through the weathering crusts remains, however, one of the outstanding questions (Halbach et al 2023 ). The standing theory for inoculation of the supraglacial environments by bacteria is that they are delivered through aerial deposition (Šantl-Temkiv et al 2018 , Cameron et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under climatic warming, increased exposure of snow-free glacial ice and melt intensity (Rounce et al, 2023) will expand the extent of the weathering crust over the coming 30 to 50 years (Stevens et al, 2022). Hence, our limited appreciation of the weathering crust's microbiome presents critical lacunae in our knowledge of supraglacial ecosystems, their biogeochemical cycles and impacts on downstream ecosystems expanding as glaciers recede (Halbach et al, 2023;Hotaling et al, 2017;Irvine-Fynn & Edwards, 2013;Varliero et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These microbial blooms, dominated by the pigmented algae Ancylonema alaskanum and Ancylonema nordenskiöldii (Lutz et al, 2018;Proch azkov a et al, 2021) have a significant effect on the darkening of the Greenland Ice Sheet (Ryan, 2017(Ryan, , 2018Stibal et al, 2017;Uetake et al, 2010;Yallop et al, 2012). Controls on the development, spatial extent, and density of microbial blooms on bare ice surfaces remain poorly understood, causing large uncertainties in how microbial coverage of bare ice surfaces might change as snowlines retreat upwards due to climatic warming (Halbach et al, 2023;Ryan et al, 2019). Previous work has demonstrated that the availability of liquid water, light, and nutrients is essential for the development of these darkening algal blooms (Anesio et al, 2017;Holland et al, 2019;McCutcheon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%